Relationship between the order of permanent tooth eruption and the predominance of motor function laterality: a cross-sectional study - Ana Veloso; Julián López Giménez; M. Carmen Vázquez; José Ramón Corcuera; Francisco Guinot; Andreu Puigdollers (Elsevier, 2021)
Objectives: To assess whether the order of permanent tooth eruption may be a useful indicator of motor function laterality. Methods: We conducted a cross-sectional study in schoolchildren aged 6-8 years old evaluated in the annual school-based routine dental health examinations conducted by the staff of the primary care centre of an urban district in Barcelona, Spain. We also evaluated hand, foot, eye, and auditory lateralities using a battery of simple exercises. Bivariate and multivariate analysis of data was performed. Results: The study sample included 388 children, 51.3% female, with a mean age of 6.5 years. Right laterality was the predominant side in every variable under study, especially in tooth eruption (310 children; 80%), handedness (349; 89.9%), and footedness (337; 86.8%). In the bivariate analysis, we found a statistically significant association of tooth eruption laterality with handedness and footedness, and of tooth eruption laterality with ocular and auditory lateralities (p < .001). In the multivariate analysis, tooth eruption laterality and foot laterality were independent variables significantly associated with hand laterality. The diagnostic accuracy of tooth eruption laterality and foot laterality in relation to hand laterality as reference, showed a similar sensitivity and positive and negative predictive values, but the specificity of dentition laterality was higher (79% versus 66%). Conclusions: Laterality in the order of dental eruption is a useful indicator of right or left motor function laterality in developing individuals that may be particularly helpful to determine the main dominance in cases of crossed laterality. Resumen: Objetivos: Evaluar si el orden de la erupción dental es un buen indicador de la lateralidad motora. Métodos: Estudio transversal en escolares de ambos sexos de 6 a 8 años sometidos a las revisiones orales rutinarias anuales realizadas en los colegios incluidos en un área de atención primaria urbana en Barcelona (España). También se evaluaron las lateralidades de manos, pies, ojos y oídos mediante una serie de ejercicios simples. Se realizaron análisis bivariantes y multivariantes de los datos. Resultados: La muestra comprendió 388 escolares, 51,3% niñas, con una edad media de 6,5 años. La lateralidad derecha predominó en todas las variables de estudio, especialmente en la dentición (310 escolares; 80%), la mano (349; 89,9%) y el pie (337; 86.8%). En el estudio bivariante se observó una asociación estadísticamente significativa (p < 0,001) entre la lateralidad de la dentición y la de la mano y el pie, así como entre la lateralidad de la dentición y las lateralidades de oído y de ojo. En el estudio multivariante, las lateralidades de la dentición y del pie se asociaron significativamente a la lateralidad de la mano. En lo concerniente a la precisión de la lateralidad de la dentición y del pie como prueba diagnóstica de la lateralidad de la mano, ambas mostraron una sensibilidad y valores predictivos positivos y negativos similares, pero la especificidad de la lateralidad de la dentición fue mayor (79% versus 66%). Conclusiones: La lateralidad en el orden de la erupción dental es un buen indicador para determinar la lateralidad motora durante el desarrollo, que podría ser particularmente útil para ayudar a precisar la lateralidad más predominante en casos de lateralidad cruzada.